Fistula between anterior rectum wall and seminal vesicles as a rare complication of low-anterior resection of the rectum - Sýkora, Radek; Krhut, Jan; Jonszta, Tomáš; Němec, David; Havránek, Ondřej; Martínek, Lubomír (Wideochirurgia i inne techniki maloinwazyjne, 2012)
Laparoscopic surgery has become a frequently used modality for rectal tumour surgery. A fistula between the rectum and lower urinary tract is one of the possible complications, with rectovesical fistulas occurring most frequently. This case report presents a 66-year-old man who underwent a laparoscopic low-anterior resection of the rectum due to the presence of a polyp with a high risk of malignant transformation. At the time of discharge on the eleventh postoperative day, the patient returned to the hospital with a fever, scrotal swelling and pain in the right hemiscrotum. These symptoms began four hours after discharge from the hospital. There was no sign of faecaluria. The presence of gas in the urinary bladder was confirmed after catheter insertion. The patient was diagnosed with a fistula between the anterior wall of the rectum and seminal vesicles. The diagnosis was based on cystoscopy findings, X-ray and computed tomography irrigography. The condition was treated conservatively by suprapubic insertion of a catheter and antibiotics. The total length of the treatment, including management of subsequent complications, was 4 months. Twelve months after the complication developed, the patient is symptom free, without urinary tract infection recurrence, and is under the care of both surgery and urology clinics. We describe the clinical symptoms, possibilities of treatment and the result of treatment of this rare complication of rectum low-anterior resection, which has never been described in the literature before.
Keywords: fistula; low-anterior resection of the rectum; seminal vesicles